An atypical case of fatal chikungunya infection in pregnancy - Panwar, Shivali; Kapur, Anu; Gupta, Dheeraj Kumar (International Journal of Research in Medical Sciences, 2016)
Chikungunya viral infection is a mosquito borne illness which is known to have a limited course and complete recovery is seen in most of the patients. However the virus has been reported to have atypical manifestations and lethal complications have been reported in patients suffering from chikungunya infection. In the present outbreak of chikungunya virus in the national capital territory of Delhi we report a case of chikungunya fever in a pregnant female with no significant medical history. The patient developed thrombocytopenia, hepatic injury and disseminated intravascular coagulation and ultimately succumbed to the illness due to cardiovascular collapse.